Answer:
The average rate of change of f(x) from x = a to x = a + h is -1
Explanation:
Average rate of the function f(x) over [a, b] is given by:
![A(x) = (f(b)-f(a))/(b-a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ouazudap4m62f8l72cv1hrk6nls2qddyve.png)
Given the function:
![f(x) = 3-x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lnp8imd7lnviiaef8ia8mtn5i1vyn1h0u8.png)
At x=a
f(a) = 3-a
At x = a+h
then;
f(a+h) = 3-(a+h) = 3-a-h
Using the formula for average rate of function:
![A(x) = (f(x+h)-f(x))/(x+h-x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/56vwrqdmpovf7fx1wjpeb1q3n0qw4d9q75.png)
Substitute the given values we have;
![A(x) = (3-a-h-(3-a))/(x+h-x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yst21nt75nuhr635v4vy07gy8biflxnfst.png)
Simplify:
![A(x) = (3-a-h-3+a)/(h)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s86jicfszbz7cqfe2txgzldqlu65dsjykg.png)
or
![A(x) = (-h)/(h) = -1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d5hiqhbgdw7lz3bpm1fqbjenq6zhodm90d.png)
Therefore, the average rate of change of f(x) from x = a to x = a + h is, -1